Three-phase adaptive reclosing method and novel fault isolation scheme for flexible interconnected distribution networks based on the soft open point - Tao Zheng; Wentao Shen (International Journal of Electrical Power & Energy Systems)
The soft open point (SOP) enables flexible interconnection in distribution networks, playing an important role in enhancing the capacity of distributed energy resource integration and balancing line loads. To address the issue of secondary impacts caused by traditional three-phase reclosing on permanent faults in distribution networks, a three-phase adaptive reclosing method based on SOP active control is proposed. This method utilizes the SOP to actively inject characteristic voltage (CV) and determines the fault properties based on the current characteristics at the SOP port. To accelerate fault recovery in distribution networks, a novel fault isolation scheme is proposed, based on feeder automation (FA) and utilizing the effective injection duration of the characteristic voltage (EIDCV) to identify the fault properties. First, the SOP adjusts the duration of the injected CV according to different fault properties. The fault properties are then locally identified by switches on the line, employing the EIDCV as a criterion. Switches can achieve adaptive fault isolation by utilizing fault property information in conjunction with the fault location information from FA. Finally, the accuracy and feasibility of the proposed method are validated through simulations on the PSCAD/EMTDC platform.